A dictionary of economics / John Black, Nigar Hashimzade, Gareth D Myles - Black, John
This authoritative dictionary covers all aspects of economics including theory, policy, and applied micro and macroeconomics on a global scale. An essential book for professional economists as well as for students and teachers of economics, business, and finance.